Permata Jingga Green Open Space as Major Component of Smart Green City in Malang - Sumardi Sumardi; Bagyo Yanuadi; Amin Setyo Leksono (Indonesian Journal of Environment and Sustainable Development, 2020)
Green open space area smart green city is developed to function as Food function, health function, philosophy function, shade function, aesthetic function and protective function which is the main function and support function to optimize the function of a green city. Green open space model management as the main element of green city Permata Jingga. a concept of a green open city, green space city vegetation type can also serve as a habitat of various types of fauna that interact with each other to build an ecosystem environment in the residential area Permata Jingga. A growing number of residence results in decreasing amount of green open space, and consequently, a reducing the amount of oxygen production. Land conservation from green open space to residence prevents trees and plants from growing well. Green open space refers to area around a certain neighborhood or in the city where trees and plants can grow. Smart green city is the solution towards lacking green open space in the cities. The era of globalization and modernization requires people to live more prosperous lives and fulfill their basic needs. Government should facilitate that using the concept of a smart city. Â Prior to solving their environmental issues, cities may not be able to have sustainable development. Smart city visions are to build sustainable, environmental-friendly, and disaster-proof smart green cities as well as to improve the governmentâ€™s ability to support the life of its people.